การวิเคราะห์การกระจายการถือครองที่ดินในภาคเกษตรกรรมของไทย ANALYSIS OF THE DISTRIBUTION OF LAND IN THE AGRICULTURAL SECTOR OF THAILAND - เอี่ยมสกุล กรีฑา; พันธวิศิษฏ์ สมบัติ; เทศวานิช จรินทร์; เพรียบพร้อม สมศักดิ์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2016)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์ 1) เพื่อวิเคราะห์การกระจายการถือครองที่ดินภาคการเกษตรกรรมของไทยและ 2) เพื่อศึกษาขนาดของการถือครองที่ดินภาคการเกษตรกรรมในการทำนาที่เหมาะสมที่จะทำให้ชาวนามีผลผลิตหรือ รายได้เพียงพอต่อปัจจัยพื้นฐานจำเป็นในการดำรงชีวิต วิธีการวิจัยโดย 1) การวิเคราะห์ข้อมูลทุติยภูมิ สำมะโน การเกษตรในปี พ.ศ. 2493, 2506, 2521, 2536 และ 2546 แล้ววัดค่าการกระจายด้วย Lorenz Curve ดัชนีการกระจุกตัวและสัมประสิทธิ์จินี และ 2) การวิเคราะห์รายได้และต้นทุนการผลิตข้าว ปีการผลิต 2551/2552 ผลการวิจัยพบว่า 1) ในปี พ.ศ. 2473 ชาวนาในภาคกลางของสยาม ไม่มีที่ดินทำกินสูงมากถึงประมาณ 32% และ จากผลการวิเคราะห์ข้อมูลการจัดสรรที่ดินจากสำมะโนเกษตรในปี พ.ศ.2493 พบว่าการถือครองที่ดินทั่วราชอาณาจักรอยู่ที่ 23.66 % ภาคใต้อยู่ที่ 30.49% ภาคกลางอยู่ที่ 28.29% ภาคเหนืออยู่ที่ 27.86% และในปี พ.ศ. 2546 พบว่า การถือครองที่ดินทั่วราชอาณาจักรอยู่ที่ 37.35% ภาคใต้อยู่ที่ 38.37% ภาคกลางอยู่ที่ 42.11% ภาค เหนืออยู่ที่ 42.32% และภาคตะวันออกเฉียงเหนืออยู่ที่ 31.80% แสดงว่า การถือครองที่ดินมีอัตราการกระจุกตัว มากขึ้น 2) เกษตรกรควรถือครองที่ดินที่ใช้ปลูกข้าวเพื่อให้มีรายได้เพียงพอต่อความต้องการขั้นพื้นฐานจำเป็นในการดำรงชีวิตเฉลี่ยในระดับประเทศอยู่ที่รายละ 19 ไร่ คำสำคัญ: Abstract The objectives of this study were to analyze: 1) the changes of land holdings in Thai agricultural sector; and 2) the appropriate size of agricultural land holdings used for paddy production sustenance of agricultural households. Research methodology: used secondary data obtained from the Agricultural Census in 1950, 1963, 1978, 1993 and 2003 as well as historical data concerning land holdings in the agricultural sector.The instruments employed in the study were Lorenz Curve, Concentration Index, and GINI Coefficient. The income level according to the poverty line also applied to investigate an appropriate farm size for sufficient income earning of paddy households. The results of the research show that: 1) the distribution of land holdings after the state recognition of private land rights in 1855 had begun concentrating until 1930 landless peasants in the Central region were 32 percents and according to the Agricultural census in 1950, the land distributions of whole kingdom was 23.66 and in 2003, it was 37.35. 2) The average land holding size of farmer household used for paddy production and sufficient income earning according to the cost and revenue analysis of paddy production in 2008 was 19 rais per household.